This expression is a perfect square trinomial. It has two answers but they don't have to be different. In this case it has to be the same - because it is a perfect square trinomial.
Answer:
Step-by-step explanation:
<u>Janet ⇒ 3 postcards ⇒ $1.05 </u>
- Cost of postcard: 1.05/3 = $0.35
<u>Rosi ⇒ 5 postcards ⇒ $1.75 </u>
- Cost of postcard: 1.75/5 = $0.35
<u>Tanya ⇒ 8 postcards ⇒ $2.80</u>
- Cost of postcard: $2.80/8 = $0.35
<u>We see in all 3 cases cost of postcard is same, the cost and numbers are proportional and the relationship is:</u>
Answer:
7(7x -4)
Step-by-step explanation:
49x-28
We can factor a 7 from each term
49x = 7*7x
28 = 7*4
7(7x -4)
Answer:
−6x+18
Step-by-step explanation:
-6(x-3)
(−6)(x+−3)
=(−6)(x)+(−6)(−3)
=−6x+18